(untitled) (Revista LIDER, 2021)
An international comparative research on 10 Latin American countries conducted by ILPES, has shown an increasing interest of national authorities on regional development. A family of territorial policies has been created, including local development, land planning, and decentralization. Nevertheless, central authorities have not realized yet the coordination challenges there are facing: between sectors and levels (national, intermediate and local). At the same time, localities and territories need a new kind of decentralized diplomacy to take advantage of these new set of opportunities. In practical an theoretical terms, it is extremely important to realize that there is a new space of confluence between local (down-top) and regional development policies (top-down) named Territorial Economic Deveolpment Policy